BIRDS AND SUSTAINABLE MANAGEMENT IN MEDITERRANEAN RIPARIAN AREAS: Bird studies in the RIPIDURABLE project - Dias, Paula (2010)
RIPIDURABLE is an INTERREG IIIC European Program involving 10 partners from Portugal, Spain, France and Greece. Scientists, technicians and local/regional authorities worked together to integrate knowledge, knowhow and practice, towards a rational conservation management of riparian zones. Birds can be used to characterize ecosystems, to monitor environmental changes or to assess results of restoration measures. We have conducted field surveys in order to assess breeding bird communities associated to riparian galleries in several watercourses, including issues as the relation with natural vegetation profiles, the influence of the surrounding matrix, the evolution with time or with habitat degradation, the effects of rehabilitation measures, and/or the importance of riparian galleries as ecological corridors for birds. Surveys at different space and time scales were carried out using standardised point count methods, on 8 watercourses in Portugal and France. We focused on different aspects of riparian breeding bird community variation: along a decreasing gradient of vegetal complexity (Tagus Basin), along an upstream-downstream gradient (Allier), with different surrounding landscapes (Sado, Guadiana and Tagus Basin), with time (Alcáçovas at a 10 years interval, Allier at 16 years interval), with management status (Vidourle), with time & management status (Rhône delta at a 12 years intervals), before & after river rehabilitation (Gandum). In addition we studied the dispersal of Barn Owls from upper Tagus Estuary along riparian corridors (TytoTagus Project), and also the importance of riparian habitats of the Guadiana basin on the autumn migration of trans-Saharan birds across the Iberian Peninsula. The RIPIDURABLE project offered the opportunity for further research currently included in national programs such as the Plan Loire Grandeur Nature which allows long term studies on riparian birds. Herein we briefly present some of the preliminary results of the bird studies carried out by partners from Portugal and France.